Cause analysis of learning management system: role of moderator in improving students’ performance - Moses, Priscilla; Wan Ali, Wan Zah; Krauss, Steven Eric (SpringerOpen, 2014)
One of the recent online learning platforms for delivering instruction being used by most universities is the Learning Management System (LMS). The LMS has shaped new ways of transferring information between moderators and learners. However, evidence suggests that the gap between actual and desired performance still exists among learners. Therefore, there is a need to probe the role of the moderator in improving the academic and technology-related performance of students. Three experienced LMS moderators were interviewed for this purpose. Fourteen categories were drawn from the interviews and were categorized into six themes. An additional factor labelled “publicise the usefulness” emerged from the study. The results draw parallels with the five factors of cause analysis in the Human Performance Technology (HPT) model.